Spa manicuring for the salon and spa - McCormick, Janet (Milady Pub., 2000)
This first-of-its-kind book will show nail salon owners and managers how transform common hand and nail services into the therapeutic beauty treatments vital to the spa experience. Learn how to integrate these upscale services into salon or day spa menus as a means of keeping pace with latest industry trends, promoting client satisfaction, and increasing revenue. Nail/hand technicians will benefit from the professional advice focusing on how to become client-oriented team players